Physicochemical stability of pemetrexed diarginine at 25 mg/mL in partially-used vials and at 3 and 12 mg/mL diluted in dextrose 5% or in sodium chloride 0.9% in polyolefin bags. Issue 2 (30th April 2022) - Nisse, Yann-Eric; Sobalak, Nathalie; Vigneron, Jean; Demore, Béatrice
Abstract: Introduction: A new pemetrexed salt, pemetrexed diarginine (PDA), was marketed by Mylan company. The product is a ready-to-dilute 25 mg/mL solution. The manufacturer indicates a 24-hour stability after dilution in dextrose 5% (D5W). The objectives were to study the stability of: PDA in D5W and 0.9% sodium chloride (0.9% NaCl) polyolefin bags at 3 and 12 mg/mL protected from light (PFL) between 2 to 8°C and at 25°C, and not PFL at room temperature; PDA vials at 25 mg/mL partially used perforated with a plastic spike PFL between 2 to 8°C and at 25°C and not PFL at room temperature. Methods: The stability study was performed by high-performance liquid chromatography coupled to a photodiode array detector. The method was validated according to International Council for Harmonisation guideline Q2(R1). Physical stability was evaluated by visual and subvisual inspection. pH values were measured. Results: PDA solutions PFL in D5W and in 0.9% NaCl at 3 and 12 mg/mL retained more than 95% of the initial concentration after 7 days at 25°C and after 28 days at 2 to 8°C. PDA ready-to-dilute 25 mg/mL solutions PFL retained more than 95% of the initial concentration after 28 days at 25°C and 2 to 8°C. PDA solutions in D5W and in 0.9% NaCl at 3 mg/mL and 12 mg/mL and PDA ready-to-dilute 25 mg/mL solutions not PFL retained more than 95% of the initial concentration after 7 days at room temperature. All samples had a pH in the range of 8.05 to 8.77. A light colouration, described in SPC, to an intense yellow-brown colouration, appeared depending on concentration and time. No precipitate was observed. Conclusion: According to the manufacturer's specifications and to the chemical stability defined as more than 95% of the initial concentration, PDA solutions in D5W and in 0.9% NaCl at 3 and 12 mg/mL and PDA ready-to-dilute 25 mg/mL solutions PFL at 25°C and not PFL at room temperature were stable for 7 days and for 28 days at 2 to 8°C. The absence of a color change as an acceptance criterion for the 25 mg/mL ready-to-dilute solution perforated with a plastic spike leads to a stability of 7 days at 2 to 8°C and 4 days at room temperature allowing the use of the vial for a preparation in advance with an optimal stability.